Closing the gap? The populist radical right and opinion congruence between citizens and MPs. (December 2022) - Kübler, Marie; Schäfer, Armin
Abstract: Some observers argue that right-wing populist parties improve representation because they speak for groups that are otherwise under-represented. In that sense, populist parties might prove beneficial for democracy. However, we lack empirical studies that support this claim. In this paper, we undertake a first step to fill this research gap. We analyse whether the electoral success of right-wing populist parties increases opinion congruence between citizens and members of parliament. Looking at the case of Germany, we will examine whether the rise of the Alternative für Deutschland (AfD), which first entered parliament in 2017, led to higher congruence between MPs and citizens. In our analyses, we use two waves of the GLES candidate study conducted in 2013 and 2017 and match those to representative surveys of the population. We use twelve items to measure opinion congruence before and after the AfD entered parliament. The analyses show that overall congruence has increased partly because AfD-parliamentarians' views on migration compensate for the previous over-representation of more liberal positions of established parties. However, beyond immigration, congruence between the AfD parliamentarians and survey respondents is not particularly high.